Entrepreneurial Orientation and its Effect on the Success of Small Businesses - Gamal Stia Putra; Wahyudi David (Journal of Business, Social and Technology, 2025)
Background: Entrepreneurial orientation (EO) has been widely recognized as a critical driver of business success, particularly for small enterprises operating in highly competitive markets. However, empirical evidence on the role of EO in supporting small business success in emerging economies, including Indonesia, remains limited. Objective: This study aims to examine the impact of entrepreneurial orientation on small business success in Indonesia, focusing on the dimensions of innovativeness, proactiveness, and risk-taking. Methods: A quantitative research approach was employed using survey data collected from 150 small business owners across various sectors. Multiple regression analysis was applied to evaluate the relationships between entrepreneurial orientation dimensions and small business success. Results: The findings indicate that innovativeness and proactiveness have a significant positive effect on small business success, while risk-taking demonstrates a moderate influence. Conclusion: These results highlight the importance of adopting innovative practices and proactive market strategies while carefully managing risk to enhance small business performance. This study contributes to the entrepreneurship literature in emerging markets and provides practical insights for entrepreneurs and policymakers in fostering sustainable small business growth.